1999
DOI: 10.1890/1051-0761(1999)009[1305:fftpio]2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Frost Followed the Plow: Impacts of Deforestation on the Climate of the United States

Abstract: The modern vegetated landscape of the United States little resembles the ''natural'' landscape prior to colonial settlement. Two 10-yr climate simulations with a global climate model using natural and modern vegetation maps for land surface boundary conditions showed that the conversion of forest to cropland in the eastern and central United States cooled climate. Mean annual surface air temperature decreased by 0.6Њ-1.0ЊC in the United States east of 100Њ W. The decrease in daily maximum temperature exceeded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
77
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 133 publications
(84 citation statements)
references
References 47 publications
3
77
0
Order By: Relevance
“…We found a 1.3°C warming in midday air temperature during the first 2 weeks following harvest. In a 10 year climate simulation, Bonan [1999] found that conversion from forest to crop resulted in a decline in midday temperature of 0.6°-1°C and 1°-3°C in the east and midwest, respectively. In a similar study, Bounoua et al [2002] reported a 0.7°-1.1°C decline in temperate regions due to land cover conversion.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…We found a 1.3°C warming in midday air temperature during the first 2 weeks following harvest. In a 10 year climate simulation, Bonan [1999] found that conversion from forest to crop resulted in a decline in midday temperature of 0.6°-1°C and 1°-3°C in the east and midwest, respectively. In a similar study, Bounoua et al [2002] reported a 0.7°-1.1°C decline in temperate regions due to land cover conversion.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past ten years, coupled atmosphere and land surface models have been developed, allowing a quantitative exploration of these interactions. The effect of land cover change on the climate of the United States has been studied by comparing current, historical, and in some cases, future land cover scenarios [Bonan, 1997[Bonan, , 1999Bounoua et al, 2002;Copeland et al, 1996;DeFries et al, 2002;Pan et al, 1999]. These studies reported regional and seasonal differences in response to land cover change.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in tropical regions, forest removal has substantial impacts on moisture regimes of remnant patches, so altering the value of what might appear to be suitable habitat patches and thus changing species demographics and distributions ( Webb et al 2006). Likewise, in temperate areas, the removal of forests promotes frost conditions and an increase in the frequency of freeze-thaw cycles (Bonan 1999). The latter have substantial impacts on organisms by either reducing growth rates or negatively affecting organismal energy balance during unexpectedly warm conditions, leading to mortality (Irwin & Lee 2003).…”
Section: Habitat Alteration (A) Habitat Alteration and Changing Climatesmentioning
confidence: 99%